Fundamentals of responsible parenthood and family planning, and the situation in Peru - Wicht Roseel, Juan (2015)
The assigned topic is very important because there must be Responsible Fatherhood in every human society. However, as much of the theoretical and practical, doctrinal and practical application difficulties arise out of a serious confusion of terms, first let's see what it means to Planned Parenthood, then try the basics, and finally see why it does not occur in Peru and what we can do about it.